(3GdJYQja HeDda OhMI GdfGTQs
(3ChdgG (B:s
(3GdMeO ddg , cJGH OhMI GdfGTQ deMGSf ef cGf HGdeZQH ef eTGjN GdbQf GdYGTQ , heDdag SjOi eMeO (B[(3Hf(B] (3YScQ GdeJhaj SfI (B986(3g` s
(3BNQgG (B:s
(3hcGf GdSdWGf CHhYHOGddg eMeO GdTjN GdTQja hGddg CYde, ef NW GdTjN GdePchQ jejfg s
(3Vef eLehY s
(3ofbdJ ef NW GdTjN YHOGdQMef Hf GdTjN eMeO GdaGSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B115 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(487 (3O(B) s
Keywords: (3GdJGQjNs